2016
DOI: 10.1021/acs.jpcb.6b07298
|View full text |Cite
|
Sign up to set email alerts
|

Inhibiting the Self-Sorting Behavior in the Blends of a Homologous Set of Polyurethane Model Compounds

Abstract: Self-sorting is the phenomenon in which there is high fidelity recognition and preference only for self and avoidance of nonself (narcissistic self-sorting). It has been observed in a number of biological systems and chiral synthetic molecules. We found that blends of biscarbamates, which are model compounds for polyurethanes, self-sort during crystallization [ J. Phys. Chem. B 2008 , 112 , 4223 - 4232 ], although these are not chiral molecules. Even if the two components in the blend differ only by a couple o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 35 publications
1
11
0
Order By: Relevance
“…In contrast to the cases of complimentary mutual self-recognition between segments of molecules mentioned above, [10][11][12][13][14][15][16][17] in the case of biscarbamates, the self-sorting occurs between homologous pairs of molecules that have the same hydrogen-bonding motifs, but differ in the length of the alkyl side chain. [21,22] Similar self-sorting was reported by Sijbesma group, using bis-ureas. [23][24][25] Wü rthner's group reviewed such self-sorting in large aromatic systems.…”
Section: Full Paperssupporting
confidence: 69%
See 4 more Smart Citations
“…In contrast to the cases of complimentary mutual self-recognition between segments of molecules mentioned above, [10][11][12][13][14][15][16][17] in the case of biscarbamates, the self-sorting occurs between homologous pairs of molecules that have the same hydrogen-bonding motifs, but differ in the length of the alkyl side chain. [21,22] Similar self-sorting was reported by Sijbesma group, using bis-ureas. [23][24][25] Wü rthner's group reviewed such self-sorting in large aromatic systems.…”
Section: Full Paperssupporting
confidence: 69%
“…As mentioned above, in our previous work, we found that the blends of any two biscarbamates in the homologous series would not mix at the molecular level (i. e., co‐crystallize) but would act as mutual diluents and depress the melting temperatures of each other. We also discussed the influence of the length of the alkyl chain on the rates of crystallization and spherulite growth of these biscarbamates from the melt in a previous publication .…”
Section: Resultsmentioning
confidence: 59%
See 3 more Smart Citations